Positive electrode material composition, positive electrode plate, preparation method of positive electrode plate, battery and electric device

CN119497917AActive Publication Date: 2025-02-21CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202280098237.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-11-11
Publication Date
2025-02-21
Estimated Expiration
2042-11-11

AI Technical Summary

Technical Problem

Existing lithium-containing phosphate batteries have low energy density and poor rate performance, making it difficult to achieve both high energy density and good rate performance.

Method used

By adjusting the graphitization degree of the cathode active material and the amount of conductive agent, ensure that 10% ≤ graphitization degree ≤ 50% and 0% ≤ conductive agent mass percentage ≤ 1% to match the migration speed of lithium ions and electrons and reduce battery life. Polarize and improve reaction rate matching.

Benefits of technology

The battery achieves both high energy density and good rate performance, especially when charging at high rates. It does not require an increase in the amount of conductive agent, or even eliminates the conductive agent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119497917A_ABST
    Figure CN119497917A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material composition, a positive electrode plate, a preparation method of the positive electrode plate, a battery and a power utilization device, the positive electrode material composition comprises a positive electrode active material and an optional positive electrode conductive agent, the positive electrode active material comprises a core part and a shell part located on at least one part of the surface of the core part, the core part comprises lithium-containing phosphate, and the shell part comprises lithium-containing phosphate. The shell part comprises a carbon material, the graphitization degree of the positive electrode active material is recorded as g1, the mass percentage content of the positive electrode conductive agent in the positive electrode material composition is recorded as w1, g1 is more than or equal to 10% and less than or equal to 50%, and w1 is more than or equal to 0% and less than or equal to 1%. The battery provided by the invention can give consideration to both high energy density and good rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Positive electrode material composition, positive electrode sheet and preparation method thereof, battery and electrical device Technical Field

[0001] The present application belongs to the field of battery technology, and specifically relates to a positive electrode material composition, a positive electrode plate and a preparation method thereof, a battery and an electrical device. Background Art

[0002] In recent years, batteries have been widely used in energy storage systems such as hydropower, thermal, wind, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. With the application and promotion of batteries, their safety performance has attracted increasing attention. Lithium-containing phosphates, represented by lithium iron phosphate, have become one of the most popular cathode active materials due to their advantages such as good safety, low price, and abundant raw material resources. However, batteries using lithium-containing phosphates have low energy density and poor rate performance.

[0003] Summary of the Invention

[0004] The purpose of the present application is to provide a positive electrode material composition, a positive electrode plate and a preparation method thereof, a battery and an electrical device, which can enable the battery to have both high energy density and good rate performance.

[0005] A first aspect of an embodiment of the present application provides a positive electrode material composition, comprising a positive electrode active material and an optional positive electrode conductive agent, wherein the positive electrode active material comprises a core portion and a shell portion located on at least a portion of the surface of the core portion, the core portion comprises a lithium-containing phosphate, and the shell portion comprises a carbon material. The degree of graphitization of the positive electrode active material is denoted as g1, and the mass percentage of the positive electrode conductive agent in the positive electrode material composition is denoted as w1, and 10%≤g1≤50%, 0%≤w1≤1%.

[0006] The inventors have discovered that when the degree of graphitization of the positive electrode active material is 10%-50% and the mass percentage of the positive electrode conductive agent in the positive electrode material composition is 0%-1%, the battery can achieve both high energy density and good rate performance. Although the mechanism is not yet clear, the inventors believe that at this point, the migration speeds of lithium ions and electrons are well matched, thereby reducing battery polarization and internal resistance, and thus achieving good rate performance. At the same time, the reaction rate of the positive electrode is easily matched with that of the negative electrode, thereby minimizing the accumulation of lithium ions on the negative electrode side during charging, which can cause increased electrolyte viscosity on the negative electrode side, slow lithium ion transport, and increased battery polarization. In addition, when the amount of positive electrode conductive agent is reduced, the amount of lithium-containing phosphate can be increased, thereby also achieving high energy density in the battery.

[0007] In any embodiment of the present application, 15%≤g1≤48% and 0%≤w1≤0.8%.

[0008] In any embodiment of the present application, 15%≤g1≤48% and 0%≤w1≤0.6%.

[0009] In any embodiment of the present application, 15%≤g1≤48% and 0%≤w1≤0.4%.

[0010] In any embodiment of the present application, 20%≤g1≤45% and 0%≤w1≤0.6%.

[0011] In any embodiment of the present application, 20%≤g1≤45% and 0%≤w1≤0.4%.

[0012] In any embodiment of the present application, 20%≤g1≤45% and 0%≤w1≤0.2%.

[0013] In any embodiment of the present application, 25%≤g1≤50% and 0%≤w1≤0.2%.

[0014] In any embodiment of the present application, 25%≤g1≤50% and w1 is 0%.

[0015] In any embodiment of the present application, 25%≤g1≤40% and w1 is 0%.

[0016] In any embodiment of the present application, 25%≤g1≤35% and w1 is 0%.

[0017] By further adjusting the graphitization degree g1 of the positive electrode active material and the mass percentage w1 of the positive electrode conductive agent, the amount of the positive electrode conductive agent can be further reduced without affecting the battery rate performance, thereby further improving the energy density of the battery.

[0018] In any embodiment of the present application, the graphitization degree g1 of the positive electrode active material is obtained by X-ray diffraction.

[0019] In any embodiment of the present application, the powder resistivity of the positive electrode active material is greater than 0 and less than or equal to 30Ω·cm, and can be optionally 0.5Ω·cm-10Ω·cm.

[0020] In any embodiment of the present application, the mass percentage of carbon element in the positive electrode active material is 0.5%-5%, and can be optionally 1%-3.5%.

[0021] When the mass percentage of carbon element is within the above range, on the one hand, the conductivity of the positive electrode active material can be improved, and on the other hand, the shell can be prevented from being too thick and reducing the gram capacity of the positive electrode active material. It can also be prevented from being too large in specific surface area of ​​the positive electrode active material and affecting the processing performance of the positive electrode sheet.

[0022] In any embodiment of the present application, the average particle size Dv50 of the positive electrode active material is 0.5 μm-10 μm, and can be optionally 1 μm-4 μm.

[0023] When the average particle size Dv50 of the positive electrode active material is within the above range, it is beneficial to improve the transmission performance of lithium ions and electrons, thereby further improving the cycle performance and rate performance of the battery; it is also beneficial for the positive electrode sheet to have a high compaction density, thereby further improving the energy density of the battery.

[0024] In any embodiment of the present application, the powder compaction density of the positive electrode active material under a force of 3 tons is ≥2.5g / cm 3 This is beneficial to improving the energy density of the battery.

[0025] In any embodiment of the present application, the lithium-containing phosphate includes one or more selected from lithium iron phosphate, lithium manganese iron phosphate, and composite materials obtained by coating and / or doping modification of the above materials.

[0026] In any embodiment of the present application, the molecular formula of the lithium-containing phosphate is LiFe 1-x-y Mn x M y PO4, 0≤x≤1, 0≤y<1, M includes one or more selected from transition metal elements other than Fe and Mn and non-transition metal elements, and can be optionally selected from one or more selected from V, Nb, Ti, Co, Ni, Sc, Ge, Mg, Al, Zr, Mn, Hf, Ta, Mo, W, Ru, Ag, Sn and Pb.

[0027] In any embodiment of the present application, the positive electrode conductive agent includes one or more selected from superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0028] In any embodiment of the present application, the mass percentage w2 of the positive electrode active material in the positive electrode material composition is ≥97.0%, and can be optionally 97.0%-98.2%, thereby obtaining a battery with high energy density.

[0029] In any embodiment of the present application, the positive electrode material composition further comprises a positive electrode binder and / or a positive electrode dispersant. The positive electrode binder is used to improve the adhesion between the positive electrode active material particles and between the positive electrode active material and the positive electrode current collector, thereby forming a good electronic network in the positive electrode sheet. The positive electrode dispersant is used to improve the stability of the positive electrode slurry, reduce the risk of cracking of the positive electrode film layer, and improve the dispersibility of the positive electrode conductive agent.

[0030] In any embodiment of the present application, the mass percentage w3 of the positive electrode binder in the positive electrode material composition is 1%-3%.

[0031] In any embodiment of the present application, the mass percentage content w4 of the positive electrode dispersant in the positive electrode material composition is 0%-0.5%.

[0032] A second aspect of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode film layer disposed on the positive electrode current collector, wherein the positive electrode film layer comprises the positive electrode material composition of the first aspect of the present application.

[0033] In any embodiment of the present application, the surface density of the positive electrode sheet is ≥300 mg / 1540.25 mm 2 , can be selected as ≥410mg / 1540.25mm 2 , ≥450mg / 1540.25mm 2 , ≥500mg / 1540.25mm 2 .

[0034] At present, the prior art believes that as the coating weight of the positive electrode sheet increases, in order not to deteriorate the internal resistance of the battery, it is necessary to increase the amount of positive electrode conductive agent. However, during the research process, the inventors found that when the positive electrode film layer includes the positive electrode material composition of the first aspect of this application, the battery can have both high energy density and good rate performance; and as the coating weight of the positive electrode sheet increases, not only is it not necessary to increase the amount of positive electrode conductive agent, but the amount of positive electrode conductive agent can be reduced, or even eliminated, and at this time, not only can the energy density of the battery be improved, but the internal resistance and rate performance of the battery will not be affected. The positive electrode material composition of the first aspect of this application helps to improve the performance of thick coating and / or high compaction density battery systems, and can enable the battery to have both high energy density and good rate performance.

[0035] In any embodiment of the present application, the surface density of the positive electrode sheet is recorded as CW, and the unit is mg / 1540.25mm 2 , the positive electrode plate satisfies 0≤100000×(w1 / CW)≤3.4, optionally, 0≤100000×(w1 / CW)≤1.8.

[0036] In any embodiment of the present application, the thickness H of the positive electrode film layer is 70 μm-145 μm, and can be optionally 90 μm-138 μm.

[0037] In any embodiment of the present application, the thickness of the positive electrode film layer is recorded as H, in μm, and the positive electrode plate satisfies 0≤100000×(w1 / H)≤14, optionally, 0≤100000×(w1 / H)≤11.

[0038] In any embodiment of the present application, the compaction density PD of the positive electrode sheet is ≥2.55 g / cm 3 , optional ≥2.58g / cm 3 , more optional ≥2.60g / cm 3 This is beneficial to improving the energy density of the battery.

[0039] In any embodiment of the present application, the positive electrode plate further includes a conductive coating located between the positive electrode current collector and the positive electrode film layer to enhance adhesion between the positive electrode film layer and the positive electrode current collector. Optionally, the conductive coating comprises conductive carbon black and a binder. Optionally, the conductive coating has a thickness greater than 0 and less than or equal to 2 μm.

[0040] In any embodiment of the present application, the resistance of the positive electrode plate is 0.1Ω-1Ω, and can be optionally 0.1Ω-0.6Ω, which is beneficial to improving the cycle performance and rate performance of the battery.

[0041] In any embodiment of the present application, the thickness of the positive electrode current collector is 10 μm-18 μm.

[0042] The third aspect of the present application provides a method for preparing a positive electrode sheet, comprising the steps of: providing a positive electrode slurry, coating the positive electrode slurry on at least one surface of a positive electrode collector, and obtaining a positive electrode sheet through drying and compacting processes, wherein the positive electrode slurry comprises the positive electrode material composition of the first aspect of the present application and a solvent.

[0043] A fourth aspect of the present application provides a battery, comprising the positive electrode material composition of the first aspect of the present application or the positive electrode plate of the second aspect of the present application or the positive electrode plate prepared by the preparation method of the third aspect of the present application.

[0044] A fifth aspect of the present application provides an electrical device comprising the battery of the fourth aspect of the present application.

[0045] The battery of the present application can take into account both high energy density and good rate performance. The electrical device of the present application includes the battery provided by the present application, and thus has at least the same advantages as the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] To more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on the drawings without inventive effort.

[0047] FIG1 is a schematic diagram of a battery cell according to an embodiment of the present application.

[0048] FIG2 is an exploded schematic diagram of an embodiment of a battery cell of the present application.

[0049] FIG3 is a schematic diagram of an embodiment of a battery module of the present application.

[0050] FIG4 is a schematic diagram of an embodiment of a battery pack of the present application.

[0051] FIG. 5 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 4 .

[0052] FIG6 is a schematic diagram of an embodiment of an electric device including the battery of the present application as a power source.

[0053] In the accompanying drawings, which are not necessarily drawn to scale, reference numerals are as follows: 1 battery pack, 2 upper housing, 3 lower housing, 4 battery module, 5 battery cell, 51 housing, 52 electrode assembly, 53 cover plate. DETAILED DESCRIPTION

[0054] Below, with appropriate reference to the accompanying drawings, the embodiments of the positive electrode material composition, positive electrode sheet and preparation method thereof, battery and electrical device of the present application are described in detail. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0055] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0056] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of the present application.

[0057] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of this application.

[0058] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0059] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0060] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0061] In this application, the terms "plurality" and "multiple" refer to two or more.

[0062] Unless otherwise specified, the terms used in this application have the common meanings that are commonly understood by those skilled in the art.

[0063] Unless otherwise stated, the values ​​of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.

[0064] As a key component of batteries, cathode active materials have a crucial impact on battery performance. Lithium-containing phosphates, represented by lithium iron phosphate, are currently one of the most popular cathode active materials. However, compared to ternary cathode active materials, batteries using lithium-containing phosphates have lower energy density. To improve the energy density of batteries using lithium-containing phosphates, a common strategy is to increase the coating weight and / or thickness of the lithium-containing phosphate. However, existing research suggests that lithium-containing phosphates have low electronic and ionic conductivity, resulting in poor battery rate capability. Furthermore, as the coating weight and / or thickness of the lithium-containing phosphate increases, the battery rate performance deteriorates. Further reducing the amount of conductive agent will accelerate the deterioration of battery performance, especially rate performance. To ensure good rate performance, the amount of conductive agent must be increased. However, this increased amount of conductive agent results in a decrease in the amount of lithium-containing phosphate, which in turn reduces the battery energy density.

[0065] Therefore, the current batteries containing lithium phosphate cannot effectively achieve both high energy density and good rate performance.

[0066] The inventors of the present application discovered during their research that by properly adjusting the degree of graphitization of the lithium-containing phosphate and the amount of the conductive agent, batteries using the lithium-containing phosphate can achieve both high energy density and good rate performance.

[0067] Positive electrode material composition

[0068] Specifically, a first aspect of an embodiment of the present application provides a positive electrode material composition.

[0069] The positive electrode material composition includes a positive electrode active material and an optional positive electrode conductive agent, wherein the positive electrode active material includes a core portion and a shell portion located on at least a portion of the surface of the core portion, the core portion includes a lithium-containing phosphate, and the shell portion includes a carbon material. The degree of graphitization of the positive electrode active material is recorded as g1, and the mass percentage of the positive electrode conductive agent in the positive electrode material composition is recorded as w1, and 10%≤g1≤50%, 0%≤w1≤1%.

[0070] The inventors of this application discovered in the process of in-depth research on battery energy density and rate performance that a key factor affecting the improvement of battery rate performance is the matching of lithium ion and electron migration speeds. When the battery is charging, lithium ions migrate from the lithium phosphate bulk phase (or lattice) to the surface, enter the electrolyte under the action of an external electric field, and then migrate to the surface of the negative electrode active material (such as graphite, etc.) through the electrolyte, and then enter the interior of the negative electrode active material (such as inserted between graphite layers). At the same time, electrons flow from the positive electrode to the negative electrode through an external circuit. When the battery is discharging, lithium ions escape from the negative electrode active material, enter the electrolyte under the action of an external electric field, and then migrate to the surface of the positive electrode active material through the electrolyte, and then enter the bulk phase (or lattice) of the positive electrode active material. At the same time, electrons flow from the negative electrode to the positive electrode through an external circuit. Therefore, the charging and discharging process of the battery requires the joint participation of lithium ions and electrons.

[0071] Lithium-containing phosphates have low electronic conductivity. To improve their conductivity, the current strategy is to coat the surface of lithium-containing phosphates with amorphous carbon. Coating with amorphous carbon can improve the conductivity of lithium-containing phosphates on the one hand, and increase the wettability of lithium-containing phosphates to electrolytes on the other, reducing battery polarization and increasing the migration rate of lithium ions. However, amorphous carbon has poor conductivity and has limited effect on improving the conductivity of lithium-containing phosphates. Therefore, in practical applications, a large amount of conductive agent is still required. Increasing the amount of conductive agent will lead to a decrease in the amount of lithium-containing phosphate, which in turn will lead to a decrease in the energy density of the battery, making it impossible for the battery to achieve both high energy density and good rate performance.

[0072] During their research, the inventors discovered that selecting a positive electrode active material with a graphitization degree of 10% or greater helps improve the conductivity of lithium-containing phosphates and enhance the rate performance of the battery. However, during further research, the inventors also discovered that a higher graphitization degree of the positive electrode active material is not necessarily better. When the graphitization degree of the positive electrode active material exceeds 50%, despite the excellent conductivity of the positive electrode active material, the rate performance of the battery using it does not continue to improve, and the rate performance of the battery will decrease to varying degrees with increasing charging current. At the same time, when the graphitization degree of the positive electrode active material exceeds 50%, the compaction density of the positive electrode sheet will also decrease, thereby reducing the energy density of the battery. In addition, when the graphitization degree of the positive electrode active material exceeds 50%, it may also lead to a deterioration in the battery's cycle performance.

[0073] The possible reason is that when the degree of graphitization of the positive electrode active material exceeds 50%, its conductivity is excellent, so the reaction rate of the positive electrode may be significantly greater than the reaction rate of the negative electrode. During charging, lithium ions will accumulate excessively on the negative electrode side, causing the viscosity of the electrolyte on the negative electrode side to increase, which is not conducive to the transmission of lithium ions and will also increase the polarization of the battery. When the degree of graphitization of the positive electrode active material exceeds 50%, the performance of the carbon material in the shell may undergo a qualitative change, and at this time, amorphous carbon tends to be converted into graphitized carbon (or crystalline carbon). Since the interlayer spacing of graphitized carbon (or crystalline carbon) is small, when it is coated on the surface of lithium-containing phosphate, it will hinder the rapid insertion and extraction of lithium ions, aggravate battery polarization, and thus lead to poor rate performance of the battery, especially poor high-rate charging performance; at the same time, when the degree of graphitization of the positive electrode active material exceeds 50%, the nanopore structure in the carbon material becomes less, thereby reducing the wettability of the lithium-containing phosphate to the electrolyte and reducing the migration speed of lithium ions, which will further aggravate battery polarization and affect rate performance; in addition, when the degree of graphitization of the positive electrode active material exceeds 50%, the shell deforms greatly during the extraction and insertion of lithium ions, which will also lead to poor structural stability of the shell and easy detachment from the surface of the lithium-containing phosphate, thereby not only reducing the conductivity of the lithium-containing phosphate, but also increasing the irreversible consumption of lithium ions, affecting the cycle performance of the battery.

[0074] In addition, the inventors of this application also noticed in their research that when the graphitization degree of the positive electrode active material is 10%-50%, if a high content of positive electrode conductive agent is also used, on the one hand, the energy density of the battery will be reduced, and on the other hand, it will be detrimental to the improvement of the battery rate performance. The possible reason is that at this time, the reaction rate of the positive electrode may be significantly greater than the reaction rate of the negative electrode. During charging, lithium ions will accumulate excessively on the negative electrode side, causing the viscosity of the electrolyte on the negative electrode side to increase, which is not conducive to the transmission of lithium ions and also increases battery polarization. In addition, it may also be due to the mismatch between the migration speeds of lithium ions and electrons. When the battery is working, the electron migration speed of the external circuit is too fast, while the migration speed of lithium ions inside the battery is slow, thereby causing excessive battery polarization. Moreover, the greater the charging current of the battery, the more obvious the battery polarization, and the worse the battery rate performance, especially the high-rate charging performance.

[0075] Further research has revealed that when the degree of graphitization of the positive electrode active material is 10%-50% and the mass percentage of the positive electrode conductive agent in the positive electrode material composition is 0%-1%, the battery can achieve both high energy density and good rate performance. Although the mechanism is not yet clear, the inventors believe that at this point, the migration speeds of lithium ions and electrons are well matched, thereby reducing battery polarization and internal resistance, resulting in good rate performance. At the same time, the reaction rate of the positive electrode is easily matched with that of the negative electrode, thereby minimizing the accumulation of lithium ions on the negative electrode side during charging, which can cause increased electrolyte viscosity, slow lithium ion transport, and increased battery polarization. Furthermore, by reducing the amount of positive electrode conductive agent, the amount of lithium-containing phosphate can be increased, thereby also achieving high energy density in the battery.

[0076] In this application, the graphitization degree of the positive electrode active material refers to the graphitization degree of the carbon material in the shell of the positive electrode active material, which has a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, the graphitization degree of the positive electrode active material can be measured using an X-ray diffractometer according to JIS K 0131-1996 and JB / T 4220-2011 to obtain the graphitization degree of the carbon material in the shell of the positive electrode active material. 002 Then according to the formula g=(0.344-d 002 ) / (0.344-0.3354)×100% to calculate the graphitization degree of the positive electrode active material. In the above formula, d 002 The interlayer spacing of the C(002) plane in the positive electrode active material crystal structure is expressed in nanometers (nm). The test instrument can be a Bruker D8 Discover X-ray diffractometer.

[0077] In the present application, when the mass percentage w1 of the positive electrode conductive agent in the positive electrode material composition is 0%, it means that the positive electrode material composition does not include the positive electrode conductive agent.

[0078] In further research, the inventors also found that by further adjusting the graphitization degree g1 of the positive electrode active material and the mass percentage w1 of the positive electrode conductive agent, the amount of the positive electrode conductive agent can be further reduced without affecting the battery rate performance, thereby further improving the energy density of the battery.

[0079] In some embodiments, 15%≤g1≤48% and 0%≤w1≤0.8%. Alternatively, 15%≤g1≤48% and 0%≤w1≤0.6%. More preferably, 15%≤g1≤48% and 0%≤w1≤0.4%.

[0080] In some embodiments, 20%≤g1≤45% and 0%≤w1≤0.6%. Alternatively, 20%≤g1≤45% and 0%≤w1≤0.4%. More preferably, 20%≤g1≤45% and 0%≤w1≤0.2%.

[0081] In some embodiments, 25%≤g1≤50% and 0%≤w1≤0.2%.

[0082] In some embodiments, 25% ≤ g1 ≤ 50% and w1 is 0%. The inventors have also found in further research that by further adjusting the graphitization degree g1 of the positive electrode active material and the mass percentage w1 of the positive electrode conductive agent, the positive electrode conductive agent can be eliminated while ensuring good rate performance of the battery, thereby further improving the energy density of the battery.

[0083] In some embodiments, 25% ≤ g1 ≤ 40% and w1 is 0%. Alternatively, 25% ≤ g1 ≤ 35% and w1 is 0%. By further adjusting the range of the graphitization degree g1 of the positive electrode active material, the battery can have good cycle performance on the basis of high energy density and good rate performance. The possible reason is that the interlayer spacing of the shell is larger at this time, its structural stability is better, and it is also beneficial to improve the electrolyte wettability of the positive electrode sheet and increase the migration speed of lithium ions, so that the battery can also take into account good cycle performance.

[0084] In some embodiments, the powder resistivity of the positive electrode active material is greater than 0 and less than or equal to 30Ω·cm, and can be optionally 0.1Ω·cm-20Ω·cm, 0.2Ω·cm-15Ω·cm, 0.5Ω·cm-10Ω·cm, 0.5Ω·cm-8Ω·cm, or 0.5Ω·cm-5Ω·cm.

[0085] In this application, the powder resistivity of the positive electrode active material has a meaning well known in the art and can be tested using methods known in the art. An exemplary test method is as follows: weigh 1-5g of the sample to be tested, adjust the depth of the feeding chamber of the powder resistivity meter, add the sample to be tested into the feeding chamber, apply pressure, and record the powder resistivity of the positive electrode active material under different pressures until the pressure continues to increase and the powder resistivity value no longer changes. Stop the test and record the powder resistivity value at this time as the powder resistivity of the positive electrode active material. The test instrument can be a PRCD 2100 powder resistivity meter from Yuanneng Technology Co., Ltd.

[0086] In some embodiments, the mass percentage of the carbon element in the positive electrode active material is 0.5%-5%. For example, the mass percentage of the carbon element in the positive electrode active material can be 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or a range consisting of any of the above values. Optionally, the mass percentage of the carbon element in the positive electrode active material is 1%-4%, 1%-3.5%, 1%-3.2%, or 1%-3%.

[0087] When the mass percentage of carbon element is within the above range, on the one hand, the conductivity of the positive electrode active material can be improved, and on the other hand, the shell can be prevented from being too thick and reducing the gram capacity of the positive electrode active material. It can also be prevented from being too large in specific surface area of ​​the positive electrode active material and affecting the processing performance of the positive electrode sheet.

[0088] In some embodiments, the average particle size Dv50 of the positive electrode active material is 0.5 μm-10 μm. For example, the average particle size Dv50 of the positive electrode active material can be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, or a range consisting of any of the above values. Optionally, the average particle size Dv50 of the positive electrode active material is 0.5 μm-8 μm, 0.5 μm-6 μm, 0.5 μm-4 μm, 0.8 μm-4 μm, or 1 μm-4 μm.

[0089] When the average particle size Dv50 of the positive electrode active material is within the above range, it is beneficial to improve the transmission performance of lithium ions and electrons, thereby further improving the cycle performance and rate performance of the battery; it is also beneficial for the positive electrode sheet to have a high compaction density, thereby further improving the energy density of the battery.

[0090] In the present application, the average particle size Dv50 of the positive electrode active material has the meaning well-known in the art, which represents the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be measured by instruments and methods known in the art. For example, it can be measured by a laser particle size analyzer in accordance with GB / T 19077-2016. The test instrument can adopt a Mastersizer 2000E type laser particle size analyzer.

[0091] In some embodiments, the powder tap density of the positive electrode active material under a force of 3 tons is ≥2.5 g / cm 3 . Thus, it is beneficial to improve the energy density of the battery.

[0092] In the present application, the powder tap density of the positive electrode active material has the meaning well-known in the art and can be measured by instruments and methods known in the art. For example, it can be measured by an electronic pressure testing machine in accordance with GB / T 24533-2009. The test instrument can adopt a UTM7305 type electronic pressure testing machine. The exemplary test method is as follows: Weigh 1 g of the sample to be tested and add it into a mold with a bottom area of 1.327 cm 2 . Apply pressure up to 3 tons, keep the pressure for 30 s, then relieve the pressure, keep it for 10 s, and then record and calculate to obtain the powder tap density of the positive electrode active material under a force of 3 tons.

[0093] In some embodiments, the specific capacity of the positive electrode active material is ≥157 mAh / g. Thus, it is beneficial to improve the energy density of the battery.

[0094] In some embodiments, the lithium-containing phosphate may include one or more of lithium iron phosphate, lithium manganese iron phosphate, and composite materials obtained by coating and / or doping modification of the above materials.

[0095] In some embodiments, the molecular formula of the lithium-containing phosphate may be LiFe 1-x-y Mn x M y PO4, 0≤x≤1, 0≤y<1, optionally, 0≤y≤0.1, M includes one or more selected from transition metal elements other than Fe and Mn and non-transition metal elements, and may be selected from one or more of V, Nb, Ti, Co, Ni, Sc, Ge, Mg, Al, Zr, Mn, Hf, Ta, Mo, W, Ru, Ag, Sn, and Pb. As an example, the lithium-containing phosphate includes one or more selected from LiFePO4, LiMnPO4, LiFe 1-x1 Mn x1 PO4 (0<x1<1, optionally, 0.5≤x1≤0.8).

[0096] In some embodiments, the mass percentage w2 of the positive electrode active material in the positive electrode material composition is ≥97.0%, and may be 97.0%-98.2%, thereby obtaining a battery with high energy density.

[0097] The present application does not particularly limit the type of positive electrode conductive agent, and materials known in the art can be used. In some embodiments, the positive electrode conductive agent may include one or more selected from superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0098] In some embodiments, the positive electrode material composition may further include a positive electrode binder. The positive electrode binder is used to improve the adhesion between the positive electrode active material particles and between the positive electrode active material and the positive electrode current collector, so that the positive electrode sheet forms a good electronic network. This application has no particular restrictions on the type of positive electrode binder. As an example, the positive electrode binder may include one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin.

[0099] Because the positive electrode material composition of the present application has a low content of the positive electrode conductive agent, the content of the positive electrode binder can also be reduced, thereby further improving the energy density of the battery. In some embodiments, the mass percentage w3 of the positive electrode binder in the positive electrode material composition can be 0.5%-3%, 1%-3%, 1%-2.5%, or 1%-2%.

[0100] In some embodiments, the positive electrode material composition may further include a positive electrode dispersant. The positive electrode dispersant is used to improve the stability of the positive electrode slurry, reduce the risk of cracking of the positive electrode film layer, and improve the dispersibility of the positive electrode conductive agent. The present application has no particular restrictions on the type of positive electrode dispersant. For example, it can be used selectively according to actual needs. As an example, the positive electrode dispersant may include one or more selected from cellulose-based compounds, polyalkylene oxides, polyvinyl alcohol, polyvinyl pyrrolidone, polyvinyl acetal, polyvinyl ether, polyvinyl sulfonic acid, polyvinyl chloride, chitosan, starch, polyacrylamide, poly(N-isopropylacrylamide), poly(N,N-dimethylacrylamide), polyethyleneimine, polyethylene oxide, poly(2-methoxyethoxyethylene), poly(acrylamide-co-diallyldimethylammonium chloride), acrylonitrile / butadiene / styrene polymer, acrylonitrile / styrene / acrylate polymer, nitrile rubber and fluororubber. In some embodiments, the mass percentage w4 of the positive electrode dispersant in the positive electrode material composition may be 0%-0.5%, which may be selected to be greater than 0 and less than or equal to 0.5%. When w4 is 0%, it means that the positive electrode material composition does not include a positive electrode dispersant.

[0101] In some embodiments, the positive electrode material composition may further include a positive electrode binder and a positive electrode dispersant.

[0102] [Method for preparing positive electrode active material]

[0103] In some embodiments, the positive electrode active material or its precursor, the organic carbon source and other optional components are mixed and placed in a protective atmosphere. By controlling the sintering temperature and / or sintering time, or adding additives such as graphite catalysts during the sintering process, a positive electrode active material with a desired degree of graphitization can be obtained.

[0104] In some embodiments, the sintering temperature may be 500°C-1200°C, for example, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C or a range consisting of any of the above values.

[0105] In some embodiments, the sintering time may be 1 hour to 20 hours, for example, it may be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours or a range consisting of any of the above values.

[0106] In some embodiments, the shielding gas may include nitrogen, argon, helium, or a combination thereof.

[0107] The present application does not particularly limit the type of organic carbon source. In some embodiments, the organic carbon source includes carbonizable organic matter and its derivatives, for example, starch, sucrose, glucose, fructose, maltose, chitosan, citric acid, alkanes, alkenes, alcohols, esters and polymers (such as polyvinyl alcohol, polyethylene, polypropylene and polypyrrole, etc.).

[0108] In some embodiments, the graphite catalyst may include a metal or a metal salt, such as nickel, nickel nitrate, or the like.

[0109] In some embodiments, the graphite catalyst may include carbonizable organic matter having a ring structure and its derivatives. Alternatively, the graphite catalyst may include one or more of naphthalene, phenanthrene, anthracene, pyrene, perylene, ferrocene, diphenylphosphine, and triphenylmethane.

[0110] In some embodiments, the added amount of the graphite catalyst is less than 5% of the mass of the positive electrode active material, and can be optionally less than 3%, less than 2%, or less than 1%.

[0111] In some embodiments, other components may be added as needed during the preparation of the positive electrode active material. For example, additives may be included so that the shell portion includes components other than the carbon material. In some embodiments, the additives may be components used to improve certain battery properties, such as additives that improve lithium ion transport performance, additives that improve the interfacial properties of the positive electrode active material, etc., as long as these additive components do not detract from the main purpose of this application.

[0112] Positive electrode

[0113] A second aspect of the embodiments of the present application provides a positive electrode plate, which includes the positive electrode material composition of the first aspect of the embodiments of the present application.

[0114] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode material composition of the first aspect of the embodiment of the present application. For example, the positive electrode current collector has two surfaces opposing each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposing surfaces of the positive electrode current collector.

[0115] In some embodiments, the positive electrode film layer may further include other positive electrode active materials for batteries known in the art. For example, the other positive electrode active materials may include one or more selected from lithium transition metal oxides and modified compounds thereof. Examples of lithium transition metal oxides may include one or more selected from lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and modified compounds thereof.

[0116] In some embodiments, the surface density of the positive electrode sheet is ≥300 mg / 1540.25 mm 2 , can be selected as ≥410mg / 1540.25mm 2 , ≥450mg / 1540.25mm 2 , ≥500mg / 1540.25mm 2 This is beneficial to improving the energy density of the battery.

[0117] Currently, the prior art suggests that as the coating weight of the positive electrode sheet increases, the amount of positive electrode conductive agent needs to be increased in order to avoid deteriorating the battery's internal resistance. However, during research, the inventors discovered that when the positive electrode film layer includes the positive electrode material composition of the first aspect of the present application, the battery can achieve both high energy density and good rate performance. Furthermore, as the coating weight of the positive electrode sheet increases, not only does the amount of positive electrode conductive agent not need to be increased, but it can be reduced or even eliminated. This not only improves the battery's energy density, but also does not affect the battery's internal resistance and rate performance.

[0118] The positive electrode material composition of the first aspect of the embodiment of the present application helps to improve the performance of thick-coated and / or high-density battery systems, and enables the battery to have both high energy density and good rate performance.

[0119] In some embodiments, the surface density of the positive electrode sheet is recorded as CW, and the unit is mg / 1540.25mm 2 , the positive electrode plate satisfies 0≤100000×(w1 / CW)≤3.4, optionally, 0≤100000×(w1 / CW)≤2.4, 0≤100000×(w1 / CW)≤1.8, 0≤100000×(w1 / CW)≤1.5, 0≤100000×(w1 / CW)≤1.

[0120] In some embodiments, the thickness H of the positive electrode film layer is 70 μm-145 μm, and can be optionally 90 μm-138 μm.

[0121] In some embodiments, the thickness of the positive electrode film layer is denoted as H, in μm, and the positive electrode plate satisfies 0≤100000×(w1 / H)≤14, optionally, 0≤100000×(w1 / H)≤11, 0≤100000×(w1 / H)≤8, 0≤100000×(w1 / H)≤6.

[0122] In some embodiments, the compaction density PD of the positive electrode sheet is ≥2.55 g / cm 3 , optional ≥2.58g / cm 3, ≥2.60g / cm 3 , ≥2.62g / cm 3 , ≥2.65g / cm 3 This is beneficial to improving the energy density of the battery.

[0123] In this application, the areal density of the positive electrode sheet has a meaning well known in the art and can be tested using methods known in the art. For example, a single-sided coated and cold-pressed positive electrode sheet can be taken (if it is a double-sided coated positive electrode sheet, the positive electrode film layer on one side can be wiped off first), punched into small discs with an area of ​​S1, weighed, and recorded as M1. Then wipe off the positive electrode film layer of the weighed positive electrode sheet, weigh the weight of the positive electrode current collector, and record it as M0. The areal density of the positive electrode sheet = (M1-M0) / S1.

[0124] In this application, the compaction density of the positive electrode sheet is a well-known meaning in the art and can be tested using methods known in the art. The compaction density of the positive electrode sheet = the surface density of the positive electrode sheet / the thickness of the positive electrode film layer.

[0125] In this application, the thickness of the positive electrode film layer has a well-known meaning in the art and can be tested using methods known in the art, such as a micrometer.

[0126] In some embodiments, the positive electrode plate may further include a conductive coating located between the positive electrode current collector and the positive electrode film layer to increase the bonding strength between the positive electrode film layer and the positive electrode current collector. Of course, in some embodiments, the conductive coating may not be provided.

[0127] In certain embodiments, the conductive coating includes conductive carbon black and a binder. The application has no particular restrictions on the type of binder, and an oily binder known in the art can be used. As an example, the binder can include one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, and tetrafluoroethylene-hexafluoropropylene copolymer.

[0128] In some embodiments, the thickness of the conductive coating is greater than 0 and less than or equal to 2 μm.

[0129] In some embodiments, the resistance of the positive electrode plate is 0.1Ω-1Ω, optionally 0.1Ω-0.8Ω, 0.1Ω-0.7Ω, or 0.1Ω-0.6Ω, which is beneficial for improving the cycle performance and rate performance of the battery.

[0130] In this application, the resistance of the positive electrode sheet is a well-known term in the art and can be tested using instruments and methods known in the art. For example, a two-probe resistance tester can be used for testing. As an example, the following test method can be used: take a 4cm×25cm sample along the longitudinal direction of the positive electrode sheet, turn on the two-probe resistance tester, select the single-point mode, and input the test area of ​​the terminal to 1540.25mm 2 20 parallel samples, 0.4t pressure, 15s interval. Place the test sample between the two probes. Click the Run button on the software and then toggle the reversing valve downward. After 15s, a data point is automatically collected. The test method is the same as above when changing each point. When 20 points are tested, the test sample is replaced and the test continues. The average of the above test results is taken as the resistance of the positive electrode.

[0131] In some embodiments, the thickness of the positive electrode current collector may be 10 μm-18 μm, but the present application is not limited thereto.

[0132] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of the metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0133] It should be noted that the various positive electrode sheet parameters (such as areal density, compacted density, thickness, etc.) given in this application refer to the parameters of the positive electrode film layer on a single side of the positive electrode current collector. When the positive electrode film layer is provided on both sides of the positive electrode current collector, the parameters of the positive electrode film layer on either side that meet the requirements of this application are considered to fall within the scope of protection of this application.

[0134] When testing the parameters of the above-mentioned positive electrode sheets, such as surface density, compacted density, thickness, and resistance, freshly prepared cold-pressed positive electrode sheets can be directly taken, or positive electrode sheets can be obtained from batteries. An exemplary method for obtaining positive electrode sheets from batteries is as follows: after fully discharging the battery, the positive electrode sheets are disassembled, and the positive electrode sheets are soaked in an organic solvent (e.g., dimethyl carbonate) for a period of time (e.g., more than 72 hours), and then the positive electrode sheets are taken out and dried at a certain temperature and time (e.g., vacuum oven at 80°C for more than 6 hours).

[0135] Preparation method of positive electrode sheet

[0136] A third aspect of the embodiments of the present application provides a method for preparing a positive electrode sheet, which can prepare the positive electrode sheet of the second aspect of the embodiments of the present application.

[0137] The preparation method includes the steps of providing a positive electrode slurry, coating the positive electrode slurry on at least one surface of a positive electrode current collector, and obtaining a positive electrode sheet through drying and compacting processes. The positive electrode slurry includes the positive electrode material composition of the first aspect of the embodiment of the present application and a solvent.

[0138] In some embodiments, the solvent may include N-methylpyrrolidone (NMP), but is not limited thereto.

[0139] Battery

[0140] A fourth aspect of the embodiments of the present application provides a battery.

[0141] The battery mentioned in the embodiments or implementations of this application refers to a single physical module that includes one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in this application may include a battery cell, a battery module or a battery pack. A battery cell is the smallest unit that makes up a battery, which can independently realize the function of charging and discharging. This application has no particular restrictions on the shape of the battery cell, which can be cylindrical, square or any other shape. Figure 1 shows a battery cell 5 with a square structure as an example.

[0142] In some embodiments, the battery cell includes an electrode assembly, and the single cell may further include an outer packaging and an electrolyte. The electrode assembly generally includes a positive electrode sheet and a negative electrode sheet, etc., and the outer packaging can be used to encapsulate the above-mentioned electrode assembly and electrolyte. The outer packaging can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS). The electrode assembly can be made by a winding process and / or a lamination process.

[0143] In some embodiments, as shown in Figure 2, the outer packaging may include a housing 51 and a cover plate 53. The housing 51 may include a bottom plate and side plates connected to the bottom plate, which together form a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 is used to cover the opening to seal the receiving cavity. The electrode assembly 52 is enclosed in the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and can be adjusted according to needs.

[0144] In some embodiments of the present application, battery cells can be assembled into a battery module. The number of battery cells contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module. Figure 3 is a schematic diagram of a battery module 4 as an example. As shown in Figure 3, in the battery module 4, multiple battery cells 5 can be arranged in sequence along the length direction of the battery module 4. Of course, they can also be arranged in any other arbitrary manner. The multiple battery cells 5 can further be fixed by fasteners.

[0145] Optionally, the battery module 4 may further include a housing having an accommodation space, and the plurality of battery cells 5 are accommodated in the accommodation space.

[0146] In some embodiments, the above-mentioned battery modules can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack. Figures 4 and 5 are schematic diagrams of a battery pack 1 as an example. As shown in Figures 4 and 5, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 is used to cover the lower box body 3 and form an enclosed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0147] [Positive electrode]

[0148] The positive electrode sheet used in the battery of the present application is the positive electrode sheet described in any embodiment of the second aspect of the present application. Therefore, the battery of the present application can achieve both high energy density and good rate performance.

[0149] [Negative electrode]

[0150] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and comprising a negative electrode active material. For example, the negative electrode current collector has two opposing surfaces in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposing surfaces of the negative electrode current collector.

[0151] The negative electrode active material can adopt negative electrode active materials for batteries that are well known in the art. As an example, the negative electrode active material includes, but is not limited to, one or more of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include one or more of elemental tin, tin oxide and tin alloy material. The present application is not limited to these materials, and other conventionally known materials that can be used as negative electrode active materials for batteries may also be used.

[0152] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. The present application does not particularly limit the type of the negative electrode conductive agent. As examples, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0153] In some embodiments, the negative electrode film layer may further optionally include a negative electrode binder. The present application does not particularly limit the type of the negative electrode binder. As examples, the negative electrode binder may include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).

[0154] In some embodiments, the negative electrode film layer may further include other additives. For example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC), a PTC thermistor material, and the like.

[0155] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0156] The negative electrode film layer is typically formed by coating a negative electrode slurry onto a negative electrode current collector, drying, and cold pressing. The negative electrode slurry is typically formed by dispersing the negative electrode active material, an optional conductive agent, an optional binder, and other optional additives in a solvent and stirring until uniformly mixed. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.

[0157] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate described in the present application may further include a conductive coating (e.g., typically composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode plate described in the present application may further include a protective layer covering the surface of the negative electrode film layer.

[0158] [Electrolytes]

[0159] The electrolyte conducts lithium ions between the positive and negative electrodes. This application does not specifically limit the type of electrolyte, and the electrolyte can be selected based on needs. For example, the electrolyte can include one or more selected from solid electrolytes and liquid electrolytes (i.e., electrolyte solutions).

[0160] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.

[0161] The electrolyte salt may include one or more selected from lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium bisoxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0162] The type of the solvent is not specifically limited and can be selected according to actual needs. In some embodiments, for example, the solvent may include one or more selected from ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0163] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives capable of improving certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.

[0164] [Isolation film]

[0165] Batteries using electrolytes, as well as some batteries using solid electrolytes, also include a separator. The separator is disposed between the positive electrode plate and the negative electrode plate, primarily to prevent short circuits between the positive and negative electrodes while allowing lithium ions to pass through. This application does not impose any particular restrictions on the type of separator, and any well-known porous structure separator with good chemical and mechanical stability can be selected. The separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different.

[0166] In some embodiments, the isolation membrane may include a base film and an optional protective coating. The base film may include a non-woven fabric, a film, or a composite film having a porous structure, and the material of the base film may include one or more of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, and polyimide.

[0167] The surface of the base film may or may not be provided with a protective coating. In some embodiments, at least one surface of the base film is provided with a protective coating, which may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic layer.

[0168] The inorganic layer includes inorganic particles and a binder, and the inorganic particles include but are not limited to one or more of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate.

[0169] The polymer layer comprises a polymer, and the material of the polymer includes but is not limited to one or more of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether and polyvinylidene fluoride.

[0170] [Preparation method]

[0171] The preparation method of the battery of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery. As an example, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, dried and injected with electrolyte, and subjected to formation, capacity and other processes to obtain a battery cell. Multiple battery cells can also be further connected in series, in parallel or in a mixed connection to form a battery module. Multiple battery modules can also be connected in series, in parallel or in a mixed connection to form a battery pack. In some embodiments, multiple battery cells can also directly form a battery pack.

[0172] Electrical devices

[0173] The embodiments of the present application also provide an electrical device, which includes the battery of the present application. The battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.

[0174] The electrical device may select a specific type of battery according to its usage requirements, such as a battery cell, a battery module, or a battery pack.

[0175] Figure 6 is a schematic diagram of an exemplary electrical device. This device is a pure electric vehicle, hybrid electric vehicle, or plug-in hybrid electric vehicle. To meet the device's high power and high energy density requirements, a battery pack or battery module can be used as a power source.

[0176] As another example, an electric device may be a mobile phone, a tablet computer, a laptop computer, etc. Such an electric device is usually required to be lightweight and thin, and may use a battery cell as a power source.

[0177] Example

[0178] The following examples describe the present disclosure in more detail. These examples are intended to be illustrative only, as various modifications and variations within the scope of the present disclosure will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing. The instruments used in the examples are commercially available.

[0179] Preparation of positive electrode active materials

[0180] The washed and dried lithium iron phosphate powder and the organic carbon source glucose are dispersed through a grinding medium for 1 hour with the aid of a dispersant alcohol until uniformly mixed. By adjusting the ratio of lithium iron phosphate powder to glucose from 80wt%:20wt% to 95wt%:5wt%, the carbon content in the final material can be controlled between 0.7% and 3.5%. The ground powder is then divided into two parts: one part is directly ground to a dry powder state, and the other part is ground to a dry powder state after adding a certain amount of stone powder glue. The two samples were then mixed and ground and dispersed for 2 hours. The evenly mixed powder was placed in a tubular furnace protected by a nitrogen atmosphere, and the nitrogen flow rate was controlled to 0.02L / min. The temperature was then first raised to 280°C at a heating rate of 2°C / min and kept warm for 2 hours to allow the glucose to crack and fully carbonize, which is conducive to full coating of the carbon material; then the temperature was continued to be raised to the sintering temperature T at 5°C / min and kept warm for t at this temperature. The graphitization degree of the carbon material was adjusted by adjusting the sintering temperature T and the holding time t. After the end, it was cooled to room temperature to obtain carbon-coated lithium iron phosphate with different degrees of graphitization.

[0181] The sintering temperature T and holding time t corresponding to the carbon-coated lithium iron phosphate with different graphitization degrees used in the following examples and comparative examples are shown in Table 1.

[0182] Table 1

[0183] Graphitization degree g1 Sintering temperature T (℃) Holding time t (h) 050065% 700815% 750820% 800825% 8001030% 85010

[0184] 35%9001040%9001250%10001255%110012

[0185] Example 1

[0186] Preparation of positive electrode

[0187] The positive electrode active material carbon-coated lithium iron phosphate (carbon content of 1.5%, graphitization degree of 15%, powder resistivity of 30Ω·cm, powder compaction density of 2.5g / cm 3 ), conductive agent carbon black (Super P), binder polyvinylidene fluoride (PVDF), dispersant polyvinyl alcohol are fully stirred and mixed in an appropriate amount of solvent NMP at a mass ratio of 97.4:0.4:2.0:0.2 to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the surface of the positive electrode current collector aluminum foil (thickness of 15μm), and after drying and cold pressing, the positive electrode sheet is obtained. The surface density of the positive electrode sheet is 410mg / 1540.25mm 2 , compacted density is 2.6g / cm 3 .

[0188] The graphitization degree of the positive electrode active material refers to the graphitization degree of the carbon material in the shell of the positive electrode active material, which can be obtained by X-ray diffractometer testing according to JIS K 0131-1996 and JB / T 4220-2011. 002 Then according to the formula g=(0.344-d 002 ) / (0.344-0.3354)×100% to calculate the graphitization degree of the positive electrode active material. In the above formula, d 002 The interlayer spacing of the C(002) plane in the positive electrode active material crystal structure is expressed in nanometers (nm). The test instrument can be a Bruker D8 Discover X-ray diffractometer.

[0189] The powder resistivity of the positive electrode active material can be tested as follows: Weigh 1-5g of the sample to be tested, adjust the depth of the powder resistivity meter's feeding chamber, add the sample to the chamber, apply pressure, and record the powder resistivity of the positive electrode active material under different pressures. The test is stopped when the powder resistivity value no longer changes as the pressure continues to increase. The powder resistivity value at this point is recorded as the powder resistivity of the positive electrode active material. A suitable test instrument is the PRCD 2100 powder resistivity meter from Yuanneng Technology.

[0190] The compacted density of the powder of the positive electrode active material can be measured by an electronic pressure testing machine according to GB / T 24533-2009. Weigh 1g of the sample to be tested and add a 2 The mold is pressurized to 3 tons, maintained for 30 seconds, then released and maintained for 10 seconds. The powder compaction density of the positive electrode active material under 3 tons of force is then recorded and calculated. The test instrument can be a UTM7305 electronic pressure testing machine.

[0191] Preparation of negative electrode sheet

[0192] The negative electrode active material graphite, binder styrene butadiene rubber (SBR), thickener sodium carboxymethyl cellulose (CMC), and conductive agent carbon black (Super P) were mixed in an appropriate amount of deionized water in a mass ratio of 96.7:1.7:0.7:0.9 to form a uniform negative electrode slurry; the negative electrode slurry was evenly coated on the surface of the negative electrode current collector copper foil (thickness 6μm), dried, and cold pressed to obtain the negative electrode sheet. The surface density of the negative electrode sheet is 180mg / 1540.25mm 2 , compacted density is 1.65g / cm 3 .

[0193] Preparation of electrolyte

[0194] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0195] Battery preparation

[0196] The prepared positive and negative electrode sheets are die-cut and slit, then wound with a separator to form an electrode assembly. The assembly is then hot-pressed, coated, tabs welded, adapters secured, and the top cover welded to the case. Afterwards, the assembly is baked to remove moisture, and the prepared electrolyte is injected for formation and capacity testing. Finally, the battery (i.e., battery cell) is completed with a blue film wrapping. The separator, located between the positive and negative electrode sheets, consists of a 5μm polyethylene film and a 15μm Al2O3 coating.

[0197] Example 2-17 and Comparative Example 2-6

[0198] The preparation method of the battery is similar to that of Example 1, except that the parameters of the positive electrode active material, the mass percentage w2 of the positive electrode active material, and the mass percentage w1 of the conductive agent used are different. Specific parameters are shown in Tables 1 and 2.

[0199] Example 18

[0200] The preparation method of the battery is similar to that of Example 4, except that the surface density of the positive electrode sheet is 300 mg / 1540.25 mm 2 , compacted density is 2.6g / cm 3 ; The surface density of the negative electrode is 135mg / 1540.25mm 2 , compacted density is 1.65g / cm 3 .

[0201] Example 19

[0202] The preparation method of the battery is similar to that of Example 4, except that the surface density of the positive electrode sheet is 500 mg / 1540.25 mm 2 , compacted density is 2.6g / cm 3 ; The surface density of the negative electrode is 225mg / 1540.25mm 2 , compacted density is 1.65g / cm 3 .

[0203] Comparative Example 1

[0204] The preparation method of the battery is similar to that of Example 1, except that amorphous carbon-coated lithium iron phosphate is used as the positive electrode active material, the mass percentage of the positive electrode active material is 95.8%, and the mass percentage of the conductive agent is 2.0%.

[0205] Test section

[0206] The performance of the battery cells prepared above was tested below. It should be noted that the batteries mentioned in the following performance tests all refer to battery cells.

[0207] (1) Battery volume energy density test

[0208] The volume energy density of the battery (Wh / L) = (battery discharge capacity × battery discharge platform voltage) / battery volume.

[0209] The discharge capacity of the battery was tested by the following method: at 25°C, the prepared fresh battery was charged to 3.65V at a constant current of 1 / 3C, and then discharged to 2.0V at a constant current of 1 / 3C, to obtain the discharge capacity of the battery.

[0210] The battery discharge platform voltage is the potential when the electrochemical reaction reaches equilibrium and can be obtained from a battery tester.

[0211] The volume of the battery is tested using the water displacement method. During the test, the battery is placed in pure water, and the volume of the water discharged is the volume of the battery.

[0212] (2) Battery rate performance test

[0213] At 25°C, the prepared fresh batteries were charged at constant currents at charging rates of 1 / 3C, 1C, 3C, and 5C to the upper cutoff voltage of the battery (corresponding to 100% SOC), then charged at constant voltage to a current of 0.05C, and then discharged at a constant current of 1 / 3C to the lower cutoff voltage of the battery (corresponding to 0% SOC), and the discharge energy of the battery at this time was recorded.

[0214] Taking the discharge energy of the battery obtained at a 1 / 3C charge rate as 100%, calculate the discharge energy retention rate of the battery at 1C, 3C, and 5C charge rates.

[0215] (3) Battery DC internal resistance test

[0216] At 25°C, the fresh battery prepared above was charged at a constant current of 1C to the upper cutoff voltage of the battery (corresponding to 100% SOC), then charged at a constant voltage to a current of 0.05C, and then discharged at a constant current of 1C to the lower cutoff voltage of the battery (corresponding to 0% SOC). The discharge capacity at this time was recorded, which was the initial discharge capacity of the battery. The battery was subjected to a cyclic charge and discharge test according to the above method until the discharge capacity of the battery decayed to 80% of the initial discharge capacity of the battery, and the test was stopped.

[0217] At 25°C, a fresh battery and a battery whose cycle capacity decayed to 80% of the initial discharge capacity were respectively taken for DC internal resistance testing, thereby obtaining the initial DC internal resistance of the battery and the DC internal resistance of the battery after cycling to 80% SOH.

[0218] The battery's DC internal resistance is measured using the following method: the battery is adjusted to 50% SOC and then pulse charged at a 4C rate for 30 seconds. The battery voltage before and after the pulse charge is recorded. Battery charging DC internal resistance (mΩ) = (voltage at the end of pulse charge - voltage before pulse charge) / charging current.

[0219] (4) Resistance test of positive electrode

[0220] The resistance of the positive electrode sheet can be tested using instruments and methods known in the art. As an example, the test method can be as follows: take a 4cm×25cm sample along the longitudinal direction of the positive electrode sheet, turn on the two-probe resistance tester, select the single-point mode, and input the test area of ​​the terminal to 1540.25mm 2 20 parallel samples, 0.4t pressure, 15s interval. Place the test sample between the two probes. Click the Run button on the software and then toggle the reversing valve downward. After 15s, a data point is automatically collected. The test method is the same as above when changing each point. When 20 points are tested, the test sample is replaced and the test continues. The average of the above test results is taken as the resistance of the positive electrode.

[0221] During the test, resistance tests were performed on freshly prepared positive electrode sheets and positive electrode sheets disassembled from the battery whose cycle capacity decayed to 80% of the initial discharge capacity, thereby obtaining the initial resistance of the positive electrode sheet and the resistance of the positive electrode sheet when the battery was cycled to 80% SOH.

[0222] An exemplary method for obtaining positive electrode sheets from a battery is as follows: After fully discharging the battery, disassemble the positive electrode sheets and clean them by soaking them in dimethyl carbonate (DMC) for at least 72 hours. After the electrolyte solvent, lithium salt, and additives in the positive electrode sheets are completely leached out, the positive electrode sheets are dried in a vacuum oven. The dried positive electrode sheets are then subjected to resistance testing using the aforementioned method.

[0223] Table 2

[0224]

[0225]

[0226] Table 3

[0227]

[0228]

[0229] From the test results in Table 3, it can be seen that when the degree of graphitization of the positive electrode active material is 10%-50% and the mass percentage of the positive electrode conductive agent is 0%-1%, the battery can have both high energy density and good rate performance. In particular, the battery also has good high-rate charging performance.

[0230] Comparative Examples 1-6 do not satisfy the requirements that the graphitization degree of the positive electrode active material is 10%-50% and / or the mass percentage of the positive electrode conductive agent is 0%-1%, and thus none of the batteries can achieve both high energy density and good rate performance.

[0231] Comparative Example 1 uses amorphous carbon-coated lithium phosphate as the positive electrode active material. When the surface density of the positive electrode sheet is high, due to the poor conductivity of the lithium-containing phosphate itself, even if up to 2% of the positive electrode conductive agent is used, the positive electrode cannot form a good conductive network, and thus the battery cannot have good rate performance. In addition, due to the high amount of positive electrode conductive agent used, the volume energy density of the battery is also reduced.

[0232] Comparative Example 2 uses a carbon-coated lithium-containing phosphate with a graphitization degree of less than 10% as the positive electrode active material, which results in a battery with high energy density, but poor rate performance. Comparative Example 3, to achieve good rate performance, adds a positive electrode conductive agent up to 1.5% to the battery in Comparative Example 2. This significantly reduces the battery's volumetric energy density and has limited improvement in discharge energy retention at 3C and 5C charge rates.

[0233] Comparative Example 4 uses a carbon-coated lithium-containing phosphate with a graphitization degree greater than 50% as the positive electrode active material. This does not allow the battery to achieve both high energy density and good rate performance. This may be because when the graphitization degree exceeds 50%, the compaction density of the positive electrode sheet decreases, which in turn leads to a decrease in the battery's energy density. Furthermore, the reaction rate of the positive electrode may be significantly greater than that of the negative electrode. During charging, lithium ions will accumulate excessively on the negative electrode side, increasing the viscosity of the electrolyte on the negative electrode side, which is detrimental to the transport of lithium ions. Furthermore, the greater the battery's charging current, the more pronounced the decline in rate performance. Combining the test results of Examples 1-7 and Comparative Example 4, it can be seen that the discharge energy retention rate of Comparative Example 4 at a 1C charge rate is close to that of Examples 1-7. However, the discharge energy retention rate of Comparative Example 4 at 3C and 5C charge rates is significantly lower than that of Examples 1-7.

[0234] Based on the test results of Examples 3-12 and Comparative Example 5, when the degree of graphitization of the carbon-coated lithium-containing phosphate is between 25% and 50%, the positive electrode conductive agent can be eliminated despite the high areal density of the positive electrode sheet. This not only further improves the energy density of the battery, but also enables the battery to have good rate performance, especially good high-rate charging performance. Furthermore, based on the test results of Examples 4, 8-12, and Comparative Example 5, it can be seen that increasing the amount of positive electrode conductive agent in this case does not further significantly improve the battery's rate performance. In addition, when the amount of positive electrode conductive agent exceeds 1%, it significantly reduces the battery's discharge energy retention rate at 3C and 5C charge rates.

[0235] Based on the test results of Examples 1-2, Examples 13-17, and Comparative Example 6, it can be seen that when the degree of graphitization of the positive electrode active material is low, the positive electrode conductive agent can be eliminated, and the battery can have good rate performance while having high energy density. However, when the positive electrode sheet also uses a lower content of positive electrode conductive agent, for example, the content of the positive electrode conductive agent is greater than 0 and less than or equal to 1%, and optionally greater than 0 and less than or equal to 0.4%, it helps to further improve the rate performance of the battery, especially the high-rate charging performance. However, when the amount of positive electrode conductive agent exceeds 1%, the discharge energy retention rate of the battery at 3C and 5C charge rates will be significantly reduced.

[0236] Based on the test results of Examples 1, 9, and 14, it can be seen that when the amount of positive electrode conductive agent is the same, increasing the degree of graphitization of the carbon-coated lithium-containing phosphate within a certain range helps to improve the rate performance of the battery. However, when the degree of graphitization of the carbon-coated lithium-containing phosphate is further increased, the rate performance of the battery, especially the discharge energy retention rate of the battery at 3C and 5C charge rates, may decrease. Therefore, by reasonably adjusting the degree of graphitization of the positive electrode active material and the amount of positive electrode conductive agent, it is helpful for the battery to better balance high energy density and good rate performance. In particular, the battery can achieve good high-rate charging performance.

[0237] Based on the test results of Examples 4 and 18-19, it can be seen that when the positive electrode sheet includes the positive electrode material combination of the present application, even if the positive electrode sheet areal density is increased, the battery can still achieve both high energy density and good rate performance. Furthermore, unlike prior art research, the amount of positive electrode conductive agent does not need to be increased, and the positive electrode conductive agent can even be eliminated.

[0238] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode material composition comprising a positive electrode active material and an optional positive electrode conductive agent, wherein: The positive electrode active material includes a core portion and a shell portion located on at least a portion of the surface of the core portion, the core portion includes a lithium-containing phosphate, and the shell portion includes a carbon material. The degree of graphitization of the positive electrode active material is recorded as g1, and the mass percentage of the positive electrode conductive agent in the positive electrode material composition is recorded as w1, and 10%≤g1≤50%, 0%≤w1≤1%.

2. The positive electrode material composition according to claim 1, wherein 15%≤g1≤48% and 0%≤w1≤0.8%, alternatively, 15%≤g1≤48% and 0%≤w1≤0.6%, more alternatively, 15%≤g1≤48% and 0%≤w1≤0.4%.

3. The positive electrode material composition according to claim 1 or 2, wherein 20%≤g1≤45% and 0%≤w1≤0.6%, alternatively, 20%≤g1≤45% and 0%≤w1≤0.4%, more alternatively, 20%≤g1≤45% and 0%≤w1≤0.2%.

4. The positive electrode material composition according to any one of claims 1 to 3, wherein 25%≤g1≤50% and 0%≤w1≤0.2%.

5. The positive electrode material composition according to any one of claims 1 to 4, wherein 25%≤g1≤50% and w1 is 0%, alternatively, 25%≤g1≤40% and w1 is 0%, more alternatively, 25%≤g1≤35% and w1 is 0%.

6. The positive electrode material composition according to any one of claims 1 to 5, wherein The graphitization degree g1 of the positive electrode active material is obtained by X-ray diffraction.

7. The positive electrode material composition according to any one of claims 1 to 6, wherein The powder resistivity of the positive electrode active material is greater than 0 and less than or equal to 30Ω·cm, and can be optionally 0.5Ω·cm-10Ω·cm; and / or, The mass percentage of carbon element in the positive electrode active material is 0.5%-5%, and can be optionally 1%-3.5%.

8. The cathode material composition according to any one of claims 1 to 7, wherein: The average particle size Dv50 of the positive electrode active material is 0.5 μm-10 μm, optionally 1 μm-4 μm; and / or, The powder compaction density of the positive electrode active material under a force of 3 tons is ≥2.5g / cm 3 and / or, The lithium-containing phosphate includes one or more materials selected from lithium iron phosphate, lithium manganese iron phosphate, and composite materials obtained by coating and / or doping modification of the above materials. Optionally, the molecular formula of the lithium-containing phosphate is LiFe 1-x- y Mn x M y PO4, 0≤x≤1, 0≤y<1, M includes one or more transition metal elements and non-transition metal elements other than Fe and Mn, and can be optionally one or more selected from V, Nb, Ti, Co, Ni, Sc, Ge, Mg, Al, Zr, Mn, Hf, Ta, Mo, W, Ru, Ag, Sn and Pb; and / or, The positive electrode conductive agent includes one or more selected from superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

9. The positive electrode material composition according to any one of claims 1 to 8, wherein The mass percentage w2 of the positive electrode active material in the positive electrode material composition is ≥97.0%, and can be optionally 97.0%-98.2%.

10. The cathode material composition according to any one of claims 1 to 9, wherein: The positive electrode material composition further includes a positive electrode binder and / or a positive electrode dispersant, Optionally, the mass percentage w3 of the positive electrode binder in the positive electrode material composition is 1%-3%; Optionally, the mass percentage content w4 of the positive electrode dispersant in the positive electrode material composition is 0%-0.5%.

11. A positive electrode sheet comprising a positive electrode current collector and a positive electrode film layer disposed on the positive electrode current collector, wherein: The positive electrode film layer comprises the positive electrode material composition according to any one of claims 1 to 10.

12. The positive electrode sheet according to claim 11, wherein: The surface density of the positive electrode sheet is ≥300mg / 1540.25mm 2 , can be selected as ≥410mg / 1540.25mm 2 , ≥450mg / 1540.25mm 2 , ≥500mg / 1540.25mm 2 .

13. The positive electrode sheet according to claim 11 or 12, wherein: The surface density of the positive electrode sheet is recorded as CW, and the unit is mg / 1540.25mm 2 , the positive electrode plate satisfies 0≤100000×(w1 / CW)≤3.4, optionally, 0≤100000×(w1 / CW)≤1.

8.

14. The positive electrode sheet according to any one of claims 11 to 13, wherein: The thickness H of the positive electrode film layer is 70 μm-145 μm, and can be optionally 90 μm-138 μm.

15. The positive electrode sheet according to any one of claims 11 to 14, wherein: The thickness of the positive electrode film layer is recorded as H, in μm, and the positive electrode plate satisfies 0≤100000×(w1 / H)≤14, optionally, 0≤100000×(w1 / H)≤11.

16. The positive electrode sheet according to any one of claims 11 to 15, wherein: The compaction density PD of the positive electrode sheet is ≥2.55g / cm 3 , can be selected as ≥2.58g / cm 3 , more optional ≥2.60g / cm 3 .

17. The positive electrode sheet according to any one of claims 11 to 16, wherein: The positive electrode plate further includes a conductive coating located between the positive electrode current collector and the positive electrode film layer. Optionally, the conductive coating comprises conductive carbon black and a binder; Optionally, the thickness of the conductive coating is greater than 0 and less than or equal to 2 μm.

18. The positive electrode sheet according to any one of claims 11 to 17, wherein: The resistance of the positive electrode plate is 0.1Ω-1Ω, and can be optionally 0.1Ω-0.6Ω; and / or, The thickness of the positive electrode current collector is 10 μm-18 μm.

19. A method for preparing a positive electrode sheet, comprising the steps of: providing a positive electrode slurry, coating the positive electrode slurry on at least one surface of a positive electrode current collector, and performing drying and compacting steps to obtain a positive electrode sheet, wherein: The positive electrode slurry comprises the positive electrode material composition according to any one of claims 1 to 10 and a solvent.

20. A battery comprising the positive electrode material composition according to any one of claims 1 to 10, the positive electrode sheet according to any one of claims 11 to 18, or the positive electrode sheet prepared by the preparation method according to claim 19.

21. An electrical device comprising the battery according to claim 20.

Citation Information

Patent Citations

  • High-conductivity ferrous phosphate lithium cathode material for lithium ion battery and preparation method thereof

    CN102324519A

  • Electrode for a secondary lithium ion battery

    CN102986081A

  • Negative active material, negative plate and battery

    CN109755493A

  • Secondary cell, and device comprising secondary cell

    CN113748539A

  • Secondary battery and apparatus comprising same

    CN113748549A

Cited By

  • Lithium ion secondary battery, battery device, power utilization device, preparation method of positive active material and preparation method of positive pole piece

    CN120109156A